Design of a torque-controlled manipulator to analyse the admittance of the wrist joint - Schouten, Alfred C.; de Vlugt, Erwin; van Hilten, J.J.Bob; van der Helm, Frans C.T. (Journal of neuroscience methods, 2006)
This paper describes the design of a torque-controlled manipulator to identify the dynamics of the wrist joint. With torque disturbances, the subject can actively control the joint angle, giving a natural task. The application of a hybrid haptic controller guarantees linearity over a large bandwidth and adjustable virtual dynamics. The haptic controller has a bandwidth of 50 Hz, meaning that the virtual dynamics are realistically felt at up to 50 Hz. To let the subject ‘feel’ the torque, disturbances as well as possible the apparent, or virtual, dynamics of the device must be small. The minimal apparent inertia of the device is 1.6 g m 2, which is of the same order as for a normal wrist, and the minimal damping and stiffness are negligible. To judge the accuracy of the manipulator, loads of known physical properties were attached and their parameters were quantified. The parameters of the loads were estimated with a maximum error of 5%. As the eigenfrequency of a (co)-contracted human wrist is approximately 15 Hz, the 50-Hz bandwidth of the haptic device is sufficient to measure all relevant dynamics of the human wrist. With this device, the dynamics of the human wrist joint can be measured under varying virtual dynamics, as well as the effect of neurological dysfunction on human motor control, for example.